Synthesis and gas permeation analysis of TiO2 nanotube-embedded cellulose acetate mixed matrix membranes - Rashid, M.H. (Springer, 2020)
Abstract: Pristine cellulose acetate (CA) membranes and CA mixed matrix membranes (MMM) embedded with titania (TiO2) nanotubes (Tnts) were synthesized by loading different weight percentages of Tnts (2, 5, 7, 10) in them by employing solution casting technique. The Tnts were prepared by hydrothermal treatment of TiO2 nanoparticles in aqueous NaOH solution. Permeability of different gases; CO2, N2, O2 and CH4, was studied across these membranes and the results were compared for pure and mixed matrix membranes. Effect of pressure on permeability of different gases was also studied. The membranes were then analyzed by Scanning Electron Microscopy (SEM), Tensile Testing (TT) and Fourier transformation infrared spectroscopy (FTIR) techniques. Results showed that homogeneous dispersion of tubes was achieved up till 5Â wt-CA loading. The average permeation of CO2 obtained was 25Â barrer at 5 bar pressure. It was further identified that the ultimate tensile strength of mixed matrix membranes was roughly 7Â times greater than the pristine membranes. Graphic abstract: Figure not available: see fulltext. Â© 2019, Institute of Chemistry, Slovak Academy of Sciences.